Unveiling the Interaction Mechanisms of Electron and X‐ray Radiation with Halide Perovskite Semiconductors using Scanning Nanoprobe Diffraction. Issue 18 (31st March 2022) - Ferrer Orri, Jordi; Doherty, Tiarnan A.S.; Johnstone, Duncan; Collins, Sean M.; Simons, Hugh; Midgley, Paul A.; Ducati, Caterina; Stranks, Samuel D.
Abstract: The interaction of high‐energy electrons and X‐ray photons with beam‐sensitive semiconductors such as halide perovskites is essential for the characterization and understanding of these optoelectronic materials. Using nanoprobe diffraction techniques, which can investigate physical properties on the nanoscale, studies of the interaction of electron and X‐ray radiation with state‐of‐the‐art (FA0.79 MA0.16 Cs0.05 )Pb(I0.83 Br0.17 )3 hybrid halide perovskite films (FA, formamidinium; MA, methylammonium) are performed, tracking the changes in the local crystal structure as a function of fluence using scanning electron diffraction and synchrotron nano X‐ray diffraction techniques. Perovskite grains are identified, from which additional reflections, corresponding to PbBr2, appear as a crystalline degradation phase after fluences of 200 e − Å − 2 . These changes are concomitant with the formation of small PbI2 crystallites at the adjacent high‐angle grain boundaries, with the formation of pinholes, and with a phase transition from tetragonal to cubic. A similar degradation pathway is caused by photon irradiation in nano‐X‐ray diffraction, suggesting common underlying mechanisms. This approach explores the radiation limits of these materials and provides a description of the degradation pathways on the nanoscale. Addressing high‐angle grain boundaries will be critical for the further improvement of halide polycrystalline film stability, especially for applications vulnerable to high‐energy radiation such as space photovoltaics. Abstract : High‐resolution microscopy using nanoprobe diffraction reveals spatially resolved changes in the local crystal structure of halide perovskite films upon irradiation with high‐energy electrons and X‐rays. High‐angle defective grain boundaries trigger the formation of degradation phases, leading to changes in the crystal structure. Targeting high‐angle grain boundaries is critical for film stability under high‐energy radiation conditions, especially for space photovoltaic applications.